Novel 3-Nitro-1H-1,2,4-triazole-based Amides and Sulfonamides as Potential anti-Trypanosomal Agents - Papadopoulou, Maria V. (2012)
A series of novel 3-nitro-1H-1,2,4-triazole-(and in some cases 2-nitro-1H-imidazole)-based amides and sulfonamides were characterized for their in vitro anti-trypanosomal and antileishmanial activities as well as mammalian toxicity. Out of 36 compounds tested, 29 (mostly 3-nitro-1H-1,2,4-triazoles) displayed significant activity against T. cruzi intracellular amastigotes (IC(50) ranging from 28 nM to 3.72 μM) without concomitant toxicity to L6 host cells (selectivity 66 to 2782). Twenty three of these active compounds were more potent (up to 58 fold) than the reference drug benznidazole, tested in parallel. In addition, 9 nitrotriazoles which were moderately active (0.5 μM ≤ IC(50) < 6.0 μM) against T. b. rhodesiense trypomastigotes, were 5 to 31 fold more active against bloodstream-form T. b. brucei trypomastigotes engineered to overexpress NADH-dependent nitroreductase (TbNTR). Finally, 3 nitrotriazoles displayed a moderate activity against the axenic form of Leishmania donovani. Therefore, 3-nitro-1H-1,2,4-triazole-based amides and sulfonamides are potent anti-trypanosomal agents.